2020
DOI: 10.1177/2325967120951077
|View full text |Cite
|
Sign up to set email alerts
|

Concussions in Soccer: An Epidemiological Analysis in the Pediatric Population

Abstract: Background: As the popularity of youth soccer has increased in the United States, more attention has been focused on the effect of concussion injuries, with recent debate on whether heading should be disallowed. There is little evidence examining the epidemiology of these injuries. Purpose/Hypothesis: The purpose of this study was to examine the prevalence and incidence of youth soccer-related concussions. We hypothesized that concussion rates will correlate with increased participation in youth soccer. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In our study incidents of head and neck injury were not reported. A great effort has been recently acknowledged to understand the extent and the impact of a brain injury on the player's quality of life [29,30]. According to previous studies, incidents of concussion were rarely registered in amateur soccer.…”
Section: Discussionmentioning
confidence: 99%
“…In our study incidents of head and neck injury were not reported. A great effort has been recently acknowledged to understand the extent and the impact of a brain injury on the player's quality of life [29,30]. According to previous studies, incidents of concussion were rarely registered in amateur soccer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the derivation of sampling weights used by the NEISS is well established and used by researchers and government agencies. 2 After being weighted, the NEISS data provide estimates for the total number of injuries related to each consumer product that is included. Variables that are recorded include treatment date, sex, race, diagnostic category, injured body part, patient disposition, and location of injury.…”
Section: Methodsmentioning
confidence: 99%
“…3 Soccer is one of the fastest-growing youth sports in the United States. 4 In the 2018 to 2019 academic year, 7.9 million athletes participated in school-sanctioned high school sports and more than 500,000 participated in NCAA sports. 5 Specific to soccer, at the high school level, there was a 17% increase in participation in men and an 11% increase in participation among women between 2010 and 2018.…”
Section: Epidemiologymentioning
confidence: 99%
“…A descriptive epidemiologic study of youth soccer throughout the United States evaluated 3285 SRC narratives for mechanism and outcome. 4 It was determined that 33% of those SRCs recorded resulted from head-to-player contact. Head-to-equipment mechanism was the cause of 24% of the SRCs.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
See 1 more Smart Citation